Pattern Formation in Evaporation Coffee Droplets: Influence of Temperature and Salt - Teng, Yanhua; Shi, Aiping; Chen, Zhaoquan; Xia, Lingyan; Xue, Changguo; Zhang, Mingxu (Asian Journal of Chemistry, 2014)
In this study, some factors influencing pattern formation in evaporation coffee droplets were investigated, such as temperature, the concentration of coffee and the mass of salt. Polarizing microscope and zoom monocular video microscope were used to investigate the pattern of coffee-ring. The results showed that the edge width of coffee-ring increased as coffee concentration increased. While the edge width of coffee-ring decreased as increased salt concentration. The results indicated that styles of pattern crystals depended on salt concentration.